Odpowiedzi

2009-12-14T21:08:53+01:00
M+n/3 =5
3m+n/2=20-n/3

3m+n=15
18m+3n=120-2n
18m+5n=120

n=15-3m
18m+75-15m=120
3m=45
m=15
n=15-45=-30


5(x-3y)=-7(3y-x)
-3(x+4)+2(3-5y)=0

6y=2x
3x+10y=6

x=3y
9y+10y=6
19y=6
y=6/19

x=18/19

1 4 1
2009-12-14T21:15:06+01:00

⅔x+y-7=0 /x3
1⅓x+4y=⁷/₃/x 3

2x+3y-21=3
4x+12y=7

2x+3y=3+21/ x -2
4x+12y=7

-4x-6y=-48
4x+12y=7

6y=-41
y=-6,83

4x+12x-6,83=7
4x-81,96=7
4x=7+81,96
4x= 88,96
x=22,24

B)m+n/3 =5 /x 3
3m+n/2=20-n/3 /x 6

3m+n=15
18m+3n=40 - 2n

3m+n=15 /x -5
18m+5n=40

-15m-5n = -75
18m+5n =40

3m = -35
m = 11,66

3m+n=15
3 x 11,66 +n =15
34,98 +n = 15
n= 15 -34,98
n= - 19,98

C) 5(x-3y)=-7(3y-x)
-3(x+4)+2(3-5y)=0

5x-15y = -21y+7x
-3x-12+6-10y=0

5x-15y+21y-7x=0
-3x-10y=12-6

-2x+6y=0 / x - 3
-3x-10y=6/ x 2

6x-18y=0
-6x-20y=12

-38y=12
y=-0,31

-3x-10x - 0,31=6
-3x+3,1=6
-3x=6-3,1
-3x= 2,9
x=-0,96